Uji Beberapa Konsentrasi Tepung Daun Sirih Hutan (Piper aduncum L.) untuk Mengendalikan Hama Gudang Callosobruchus chinensis L. - Rustam, Rusli; Salbiah, Desita; Abidin, Fitriani (Jurnal Agro Teknologi Tropika, 2016)
Mung bean (Phaseolus radiatus L.) is one of the food commodities which is quite important for human because its nutrients contains such as protein, vitamin B1 and carbohydrate. Mung bean storage has many problem such as the damage caused by Callosobruchus chinensis L.. The damage by C. chinensis L. on mung bean could reach up to 70%. The use of Piper aduncum L. leaf as an alternative insecticide for fumigant is expected to become more effective and environmentally. This study aims to find and obtained the best concentration of P. aduncum L. leaf powder to controlling C. chinensis L. in mung bean storage. The research was conducted at the Laboratory of Plant Pests Faculty of Agriculture, University of Riau from Febuary to May 2015. This research using completely randomized design (CRD) with 4 treatments and 5 replications. The treatment used of some concentration of P. aduncum L. leaf powder are; 0 g/ 50 g mung beans, 1 g/ 50 g mung beans, 3 g/ 50 g mung beans and 5 g/ 50 g mung beans. The result of this study is the concentration of 5 g/ 50 g mung beans better, because it was able to C. chinensis L. mortality to 82%.